确保医疗和科研用途国际管制药物 充分供应的进展情况 - International Narcotics Control Board (United Nations, 2019)
The preamble of the Single Convention of 1961 highlights the concern of States for the health and welfare of humankind. This fundamental assertion is followed by the recognition of the medical use of narcotic drugs and their indispensable role in the relief of pain for which countries needed to ensure the availability and to make adequate provision. These principles were reaffirmed in the Convention on Psychotropic Substances of 1971 in which it was added that, while it was necessary to restrict the use of controlled substances to legitimate purposes, their availability should not have been unduly restricted. After almost sixty years since that official proclamation, the goal of ensuring availability is still elusive in many countries where people still suffer or die in pain or do not have access to the medications they need. The imbalance in the availability of opioid analgesics is particularly worrying as the data show that many of the conditions requiring pain management, particularly cancer, are prevalent and increasing in low- and middle-income countries.